Palaeointensity determinations from historical and Holocene basalt lavas in Iceland (Dataset) ... - Tanaka, Hidefumi; Hashimoto, Yuko; Morita, Noriko (Magnetics Information Consortium (MagIC), 2013)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Palaeointensity determinations from historical and Holocene basalt lavas in Iceland ...